Emerging role of Twist1 in fibrotic diseases. Issue 3 (5th January 2018) - Ning, Xiaoxuan; Zhang, Kun; Wu, Qingfeng; Liu, Minna; Sun, Shiren
Abstract: Epithelial–mesenchymal transition (EMT) is a pathological process that occurs in a variety of diseases, including organ fibrosis. Twist1, a basic helix–loop–helix transcription factor, is involved in EMT and plays significant roles in various fibrotic diseases. Suppression of the EMT process represents a promising approach for the treatment of fibrotic diseases. In this review, we discuss the roles and the underlying molecular mechanisms of Twist1 in fibrotic diseases, including those affecting kidney, lung, skin, oral submucosa and other tissues. We aim at providing new insight into the pathogenesis of various fibrotic diseases and facilitating the development of novel diagnostic and therapeutic methods for their treatment.